Student Character in Preventing National Degradation - Hammam Nur Hasan; Evan Rama Digna (Konsultan Jurnal Ilmiah Indonesia, 2026)
This study aims to analyze the role of student character in preventing the increasingly strong national degradation caused by technological developments, social change, and the weakening of national values. Students, as the intellectual generation, have a moral responsibility to maintain the stability of the nation's character through critical, ethical, and national-minded attitudes. A qualitative approach was used to explore the phenomenon of student character based on various literature reviews from 2020–2025. The results indicate that student character formation is influenced by the family environment, campus, organizations, digital media, and spirituality. These factors significantly contribute to strengthening student integrity, thereby preventing moral and social degradation. This study emphasizes that character strengthening cannot be achieved instantly but requires a continuous process involving the active participation of students, educators, and the social environment. With strong character, students have the potential to become agents of change in upholding the nation's noble values ​​and encouraging the creation of a future generation with integrity.